'Transnational film, transnational memory? Collective remembrance in recent pan-asian war films'. Issue 2 (4th May 2021) - Weiss, Amanda
ABSTRACT: This paper explores the conflict over memory in East Asia by analyzing three pan-Asian film productions that attempt to produce a shared transnational memory of World War II: Purple Sunset (China, 2001), Distant Bonds (Japan, 2009), and My Way (South Korea, 2011). Using Hjort's taxonomy of transnational cinemas (2009), it argues that all three productions appeal to pan-Asian transnational memory through affinitive transnationalism (transnational memory based on shared cultural heritage), but their overall transnational strategies diverge into cosmopolitan, modernizing, and globalizing transnationalism. Each strategy works to varying success for domestic and international audiences, suggesting that the cultural production of transnational memory remains elusive in the East Asian context. This paper ends with the question of whether cohesive transnational war memory is possible in East Asian cinema, and more broadly, how a stronger trend of pan-Asian transnational filmmaking might emerge outside of contested topics like World War II.